Ulinastatin: A Potential Alternative to Glucocorticoid in the Treatment of Severe Decompression Sickness - Meng, Wen-tao; Qing, Long; Li, Chun-zhen; Zhang, Kun; Yi, Hong-jie; Zhao, Xu-peng; Xu, Wei-gang (Frontiers in Physiology, 2020)
Inflammatory reaction is the crux in various clinical critical diseases including decompression sickness (DCS). Ulinastatin (UTI), a potent anti-inflammatory agent, has been used clinically, including as a substitution for steroids. This study aimed to explore the potential effects of UTI upon DCS in a rabbit model. Eighty-eight rabbits were subjected to simulated diving to 6 atmospheres absolute (ATA) for 60 min with 2.5-min decompression. Three doses of UTI (15/7.5/3.75×105 U/kg) or saline were intravenously administered immediately following decompression. Circulating bubbles were monitored for 3 h following decompression and DCS signs were evaluated for 24 h. Blood was sampled 8 times during 72 h after decompression for inflammatory, endothelial, oxidative and routine blood indices. Lung tissues were also sampled for evaluating endothelial function. Another 6 rabbits were used as Normal controls. In the high dose UTI group the mortality, general morbidity and incidence of severe DCS was decreased from 31.25% to 9.38% (P=0.030), 84.38% to 62.50% (P=0.048) and 46.88% to 21.88% (P=0.035), respectively. The high dose of UTI significantly postponed the occurrence of DCS (P=0.030) and prolonged survival time (P=0.009) compared with the Saline group, and significantly ameliorated inflammation responses, endothelial injuries and oxidative damage. The other two doses of UTI showed promise but had no statistical significance. The results strongly suggest the benefit of UTI on DCS, especially for severe cases. Large doses are needed to achieve significant effects. UTI may be a potential ideal pharmacological candidate for the treatment of severe DCS.